Tics y su incidencia en el desarrollo del aprendizaje significativo en el área de matemáticas en los estudiantes del 1er año de bachillerato de la Unidad Educativa Eugenio Espejo del cantón Babahoyo, Provincia Los Ríos - Rosero Jara, Joel Fabian (2020)
The research work tries to know what incidence the Tics have in the significant learning of the students of 1st Baccalaureate of the Educational Unit "Eugenio Espejo", when used in the area of mathematics. For this, one must first know what the so-called Tics are, because when referring to these, not only is technology talked about, but also about the resources that can be used through said technology. This research focuses on the Tics as a teaching tool that improves meaningful learning, since the area to work is mathematics and the contents must reach the student with total clarity, in addition, they are more interesting for students to be shown interactively through the use of technology. To achieve this, the 98 first year Baccalaureate students and the only Mathematics teacher of that cycle were taken as a reference population, resulting in a total population of 99. The necessary statistical tests were performed, using the survey technique to Questionnaire way as a collection instrument. This survey consisted of 10 questions addressed to the students and 10 questions addressed to the teacher, all this with the purpose of verifying the relevance of the use of the Tics, and analyzing the degree of knowledge that both the teacher and the students have about the use of these. Once the survey was conducted, an analysis was made that more than 50% of the students surveyed know what the Tics are, making it more feasible to include them in the teaching process